Food, nutrition, and population health: exploring the role of food as preventive medicine - Zigmont, Victoria A.; Causey, Traci (2019)
Keywords: dept.pch

Trends in Weight among Undergraduate Students in a Northeast Public University - Evans, Marian; Zigmont, Victoria A. (Journal of Public Health Issues and Practices, 2020)
Objective: Increasing BMI, overweight, and obesity are urgent and grave problems in the US. The goal of this study is to begin to understand trends in overweight and obesity among undergraduate students in the U.S. to assist in informing public health education and health promotion practices. Methods: Data on self-reported weight and height were collected in 2012, 2014, and 2016 from randomly selected college students who were enrolled in a public university in Northeast US. Spearman's Rank Order Test was used to evaluate trends within specific demographic categories. Results: BMI increased for almost all studentsfrom 2012-2016. Groups with significant increases in BMI included: males, females, sophomores, and seniors. Conclusions: Results suggest the need for interventions to reduce increases in overweight and obesity that are experienced during college years. College is a critical transitional time when students adopt health behaviors that they continue into adulthood. Increasing BMI in college students indicates a need for additional research to understand the factors that contribute to the increasing trend of overweight and obesity in this population. College is an optimal setting for implementation of effective interventions that can help prevent BMI increases in this population and establish healthy behaviors for the future. Keywords: Overweight, Obesity, College Students, BMI, Spearman’s Rank, Interventions
Keywords: dept.pch; peer-reviewed

Undergraduate food insecurity, mental health, and substance use behaviors - Neal, Latasha; Zigmont, Victoria A. (Nutrition and Health, 2022)
Objective: Recent epidemiological research has found food insecurity to be a growing public health concern among college students. This study investigated food insecurity, mental health, and substance use behaviors among state university undergraduate students. Study Design: Cross-sectional survey. Methods: This was a secondary data analysis of the Student Health Survey. Undergraduate participants ( n = 589) completed the paper-based survey, which had an 84% response rate overall. Results: Approximately 38.5% of students were considered food insecure, 24.8% experiencing low food security, and 13.8% experiencing very low food security. Having a diagnosis of depression, experience of depressive symptoms, and marijuana use in the past 30 days were associated with food insecurity. Conclusion and Implications: Food insecurity is a serious health concern for college students. The results of this study indicate collocating food security and counseling services may enhance existing student resources to better support students facing food and nutrition insecurity, substance use, and depression.
Keywords: SCSU-student; dept.pch; dept.psy

Understanding food insecurity among collegiate athletes: a qualitative study at a public university in New England - Anziano, Jennifer; Zigmont, Victoria A. (Journal of Athletic Training, 2024)
Context: Authors of previous research at a public university in New England, where the current study takes place, showed that approximately one-third of undergraduate students have experienced some aspect of food insecurity. More recent investigators at this university revealed that students who were members of a sport team were 4 times more likely to be food insecure than their peers who were not on a sport team. The estimated prevalence of student-athlete food insecurity from other previous research studies ranged from 14% to 32%. Objective: To understand the contributing factors to food insecurity among collegiate athletes. Design: Qualitative study. Setting: A public university in New England. Patients or Other Participants: Data are presented for 10 collegiate athletes who experienced some level of food insecurity according to the United States Department of Agriculture Six-Item Short Form. Data Collection and Analysis: Data were collected using a brief demographic questionnaire and semistructured interviews. Results: Contributing factors were a lack of time, special dietary needs, limited campus dining options, and limited access to transportation or kitchens. Coping strategies were managing time and resources, buying cheaper foods, and skipping meals. Food insecurity negatively affected students' athletic performance. The athletes struggled to balance their athletic and academic schedules and obtain a diet that allowed them to meet their performance goals. Conclusions: Additional and innovative programming is needed to support food-insecure student-athletes. © by the National Athletic Trainers' Association, Inc.
Keywords: academic performance; athletic performance; dept.pch; diet; nutrition; open-access; peer-reviewed

The impact of caloric information on college student's fast food purchasing intentions - Zigmont, Victoria A; Bulmer, Sandra Minor (American journal of health education, 2015)
Background: Fast food establishments are available on many college campuses and, as a result, many students consume foods that are high in calories and contribute to unhealthy weight gain. Purpose: This study measured college students' knowledge of the calorie content for fast food items and whether the provision of calorie information for those foods influenced their future purchasing intentions. Method: Randomly selected undergraduate college students (N = 201) completed an online survey that measured baseline knowledge of calorie content for a fast food item and intention to purchase that item in the future. After provision of accurate calorie information, students were posttested for intention to purchase that item in the future. Results: The majority of students underestimated calorie content for fast food items. After receiving accurate calorie information, those who initially underestimated calorie content were significantly more likely to change their intention to purchase that food item in the future. Discussion: Many college students are interested in avoiding high-calorie fast food items but are uninformed about calorie content. Translation to Health Education Practice: Colleges should provide calorie information for fast food items at the point of purchase so that students can make informed decisions that will promote their health. © 2015, Copyright © SHAPE America.
Keywords: dept.hhs; dept.pch

Differences in health behaviors related to overweight/obesity by race/ethnicity in a diverse urban commuter college - Rupp, Kristie; Schnoll, Roseanne; Zigmont, Victoria A. (Journal of American College Health, 2020)
Objective: To examine health behaviors associated with overweight/obesity by race/ethnicity at a diverse urban college. Participants: 270 undergraduates (77.0% female; 26.7% non-Hispanic white) and median body mass index (BMI) of 23.1 kg/m2. Methods: A questionnaire about health-related behaviors as part of the “Get Fruved” project was used to measure health behaviors (sugar sweetened beverage (SSB), fruit and vegetable consumption, physical activity, stress, and sleep) by race/ethnicity. Multivariable logistic regression was used to assess the adjusted odds of engaging in positive health-related behaviors. Results: Non-Hispanic black and Hispanic students were 64% and 59% less likely to consume lower amounts of SSB. Hispanic students were 83% and 81% less likely to meet vegetable and fruit recommendations. Non-Hispanic black and other (including biracial) had reduced odds of meeting vegetable recommendations (AOR = 0.18 and 0.28). Conclusions: Disparities in SSB, fruit, and vegetable consumption represent potential intervention targets to improve health behaviors among racial/ethnic minorities. © 2020 Taylor & Francis Group, LLC.
Keywords: College; dept.hms; dept.pch; health behavior; peer-reviewed; race/ethnicity

Exposure to Di-2-ethylhexyl phthalate (DEHP) and infertility in women, NHANES 2013-2016. - Trnka, Brittany; Polan, Maya; Zigmont, Victoria A. (Reproductive toxicology (Elmsford, N.Y.), 2021)
Di-2-ethylhexyl phthalate (DEHP) exposure is widespread in the general population and previous research has suggested that it contains endocrine-disrupting properties that can adversely affect the reproductive health system. The objective of this study was to use the 2013–2016 National Health and Nutrition Examination Survey (NHANES) data to assess the potential association between DEHP exposure and infertility in women. Using a nationally representative, cross-sectional study design, we used multiple logistic regression to measure the association of urinary metabolites of DEHP with self-reported history of infertility among women. Four metabolites of DEHP were examined: mono(2-ethylhexyl)phthalate (MEHP), mono(2-ethyl-5-hydroxy-hexyl)phthalate (MEHHP), mono(2-ethyl-5-oxy-hexyl) phthalate (MEOHP), and mono(2-ethyl-5-carboxy-pentyl)phthalate (MECPP). These metabolites were calculated into a molar sum of DEHP (∑DEHP) and split into quartiles for analysis. After adjusting for age and race, ∑DEHP was associated with increased odds of infertility for the second quartile (AOR = 2.35, 95% CI [1.24,4.44], p = 0.01) and third quartile (AOR = 2.83, 95% CI [1.57, 5.10], p ¡ 0.01) when compared to the first quartile (reference). The adjusted OR for the highest quartile of ∑DEHP found no association and it was not statistically significant (AOR = 0.99, 95 %CI [0.57, 1.73], p = 0.98). The findings of this study add to the already complex existing literature on phthalate exposure and infertility. These findings warrant further population-based cohort studies on phthalate exposure and their relationship to infertility in humans. © 2021 Elsevier Inc.
Keywords: Adult; Article; Cross-Sectional Studies; Diethylhexyl Phthalate; Endocrine Disruptors; Environmental Exposure; Environmental Pollutants; Female; Humans; Infertility; Male; Middle Aged; Nutrition Surveys; Phthalic Acids; Young Adult; adult; cohort analysis; controlled study; cross-sectional study; dept.pch; drug urine level; electrospray mass spectrometry; endocrine disruptor; environmental exposure; exposure; female; female infertility; high performance liquid chromatography; human; infertility; limit of detection; major clinical study; male; middle aged; mono(2 ethyl 5 carboxy pentyl)phthalate; mono(2 ethyl 5 hydroxy hexyl)phthalate; mono(2 ethyl 5 oxy hexyl)phthalate; mono-(2-ethylhexyl)phthalate; nutrition; peer-reviewed; phthalic acid; phthalic acid 2 ethylhexyl monoester; phthalic acid bis(2 ethylhexyl) ester; phthalic acid derivative; pollutant; questionnaire; sensitivity analysis; toxicity; unclassified drug; young adult

Understanding the why of college student food insecurity - Zigmont, Victoria A.; Linsmeier, Abigail M.; Gallup, Peggy (Journal of Hunger & Environmental Nutrition, 2019)
This study sought to understand why college students are food insecure and what the impact is on their academics. A generic qualitative study design was utilized that consisted of written surveys and semi-structured interviews. Participants (n = 19) self-identified as food insecure based upon their answers to the 6-item Short Form Food Security Survey Module. Two researchers independently coded the data for themes and patterns. Risk factors for food insecurity included finances, time, and lack of resources/skills to provide for healthy eating. Time and money put commuter students at risk for food insecurity. While students within this convenience sample reported negative impacts on their academic achievement from food insecurity, their coping mechanisms prioritized cost and convenience over food quality, possibly exacerbating their situation.College food insecurity is a complex issue and raw measurements may not paint a complete picture. Conflicting priorities in addition to income and time pressures mean that interventions should be tailored from current approaches. Colleges may need to find unique ways to ensure food security for at risk students within financial aid packages and/or university programs to ensure student success.
Keywords: College students; dept.pch; food insecurity; higher education; hunger; peer-reviewed; university students

Flu vaccinations: College campus not making the grade. A study of influenza vaccination at an urban public university. - Kreiger, Joan E; Zigmont, Victoria A.; Michalski, Carrie D; Borgognone, Kristen S (Journal of American college health : J of ACH, 2021)
Objective: Even healthy college students are vulnerable to severe complications associated with seasonal influenza (flu). Despite national directives to increase influenza vaccination compliance, college campuses remain woefully below national goals. This study aimed to identify factors correlated with the decision to voluntarily receive an influenza vaccine. Additionally, students’ reasons for non-vaccination were also examined. Participants: 1021 undergraduate students across four professional schools. Methods: A representative cross-sectional survey was conducted at a public, urban university. Results: The survey measured self-reported influenza vaccination: an overall influenza vaccination rate of 38% was identified. Student characteristics associated with increased influenza vaccination included students’ enrollment in academic health disciplines; being female; human papillomavirus (HPV) vaccination; and no marijuana use in the last month. Barriers to influenza vaccination included contraindications, mistrust issues, and personal reasons. Conclusion: Universities that can identify facilitators and barriers to voluntary influenza vaccination can assist with program initiatives to improve influenza vaccination compliance rates. © 2021 Taylor & Francis Group, LLC.
Keywords: dept.hms; dept.nur; dept.pch; peer-reviewed

Examining Delivery Method and Infant Feeding Intentions between Women in Traditional and Non-Traditional Prenatal Care. - Risisky, Deb; Chan, Ronna L; Zigmont, Victoria A; Asghar, Syed Masood; DeGennaro, Nancy (Maternal and child health journal, 2018)
Introduction The purpose of the study is to evaluate delivery method and breastfeeding initiation in women enrolled in group prenatal care (CenteringPregnancy) and in traditional prenatal care. Methods Data were obtained from medical records of a hospital-based midwifery practice in south central Connecticut that offered both types of prenatal care programs. Medical information from 307 women enrolled in this practice was included in the analysis. Out of the 307, 80 were enrolled in group prenatal care. Socio-demographic, lifestyle, and previous and current obstetrical information from medical records formed the basis of comparison. Bivariate and logistic regression analyses were carried out. Results Women in Centering had fewer planned cesarean sections (1.3 vs. 12.8%) and had a higher breastfeeding initiation (88.7 vs. 80.0%). However, Centering women were found to have a higher portion of unplanned cesarean sections (27.5 vs. 11.0%). Both the unadjusted and the adjusted odds ratios of having a cesarean planned delivery were lower in the group care. Women in Centering had 2.44 (95% CI 1.05, 5.66) times the odds of breastfeeding initiation compared to the odds for women in traditional prenatal care after adjusting for maternal age, smoking status, gestation and race. Discussion CenteringPregnancy can have positive impact for the woman and baby. This program implementation saw lower rates of elective cesarean sections and increased breastfeeding compared to women in traditional care.
Keywords: *Breast Feeding/px [Psychology]; *Breast Feeding/sn [Statistics & Numerical Data]; *Cesarean Section/sn [Statistics & Numerical Data]; *Intention; *Mothers; *Prenatal Care/mt [Methods]; Adult; Breast Feeding; Breastfeeding; CenteringPregnancy; Cesarean Section; Cesarean section; Connecticut; Female; Group Processes; Humans; Infant; Infant, Newborn; Intention; Mothers; Mothers/px [Psychology]; Mothers/sn [Statistics & Numerical Data]; Pregnancy; Prenatal Care; Prenatal care; Standard of Care; adult; behavior; breast feeding; cesarean section; comparative study; dept.pch; female; group process; health care quality; human; infant; mother; newborn; peer-reviewed; pregnancy; prenatal care; procedures; psychology; statistics and numerical data

An Evaluation of Reach for a Work Site Implementation of the National Diabetes Prevention Program Focusing on Diet and Exercise. - Zigmont, Victoria A; Shoben, Abigail B; Kaye, Gail L; Snow, Richard J; Clinton, Steven K; Harris, Randall E; Olivo-Marston, Susan E (American journal of health promotion : AJHP, 2018)
PURPOSE: Our objective is to evaluate the "reach" component of the Reach Effectiveness Adoption Implementation Maintenance (RE-AIM) framework by comparing prediabetics who were and were not interested in enrolling in a free work site diabetes prevention program (DPP) during the first year of the program. Reach is defined as the proportion of eligible participants who enroll in a health program., DESIGN: A cross-sectional study design was used., SETTING: The setting was a large health system in the Midwest., PARTICIPANTS: Prediabetic health plan enrollees and spouses (N = 2158)., MEASURES: An online health survey, annual voluntary biometric screenings delivered by a trained health-care professional using standardized protocols via point-of-care testing, and records from the DPP office were the sources of data for this study., ANALYSIS: Health behaviors and biometric screening results were simultaneously compared using multivariable logistic regression., RESULTS: The study population was 63% female, 79% white, and 16% black, and the mean age was 50.2 years (SD = 10.2). The reach of this program was 10%. Prediabetics were more likely to express interest in the DPP, if they were female (adjusted odds ratio [AOR]: 2.4; 95% confidence interval [95% CI]: 1.55-3.72; P < .001), black (AOR = 2.23; 95% CI: 1.43-3.47; P < .001), older in age (AOR: 1.08; 95% CI: 0.99-1.17; P = .05), or had a high-risk waist circumference (AOR = 1.44; 95% CI: 0.98-2.13; P = .07), lower self-efficacy to make healthy changes (AOR = 0.48; 95% CI: 0.26-0.91; P = .03), and 5 or more doctor visits in the last year (AOR = 2.13; 95% CI: 0.99-4.57; P = .05), after controlling for other covariates., CONCLUSION: Current recruitment and implementation strategies are reaching only a small group of individuals who are not representative of the larger prediabetic population. These findings inform future engagement strategies, and we recommend that public health practitioners evaluate reach to ensure that health promotion programs are of high value.
Keywords: *Diabetes Mellitus, Type 2/pc [Prevention & Control]; *Diet/px [Psychology]; *Exercise/px [Psychology]; *Health Promotion/mt [Methods]; *Healthy Lifestyle; *Occupational Health; *Workplace/px [Psychology]; Adult; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Diet; Exercise; Female; Health Promotion; Healthy Lifestyle; Humans; Male; Middle Aged; Midwestern United States; Occupational Health; Program Evaluation; RE-AIM framework; United States; Workplace; adult; cross-sectional study; dept.pch; diabetes prevention program; diet; evaluation study; exercise; female; health promotion; healthy lifestyle; human; male; middle aged; non insulin dependent diabetes mellitus; occupational health; peer-reviewed; prediabetes; procedures; program evaluation; psychology; work site health promotion; workplace

Statin users have an elevated risk of dysglycemia and new‐onset‐diabetes - Zigmont, Victoria A.; Shoben, Abigail B.; Lu, Bo; Kaye, Gail L.; Clinton, Steven K.; Harris, Randall E.; Olivo‐Marston, Susan E. (Diabetes/Metabolism Research and Reviews, 2019)
Keywords: dept.pch; dysglycemia; inverse probability weighting; peer-reviewed; statin use; survival analysis; type 2 diabetes mellitus

Associations between prediagnostic blood glucose levels, diabetes, and glioma. - Schwartzbaum, Judith; Edlinger, Michael; Zigmont, Victoria; Stattin, Par; Rempala, Grzegorz A; Nagel, Gabriele; Hammar, Niklas; Ulmer, Hanno; Foger, Bernhard; Walldius, Goran; Manjer, Jonas; Malmstrom, Hakan; et al. (Scientific Reports, 2017)
Previous literature indicates that pre-diagnostic diabetes and blood glucose levels are inversely related to glioma risk. To replicate these findings and determine whether they could be attributed to excess glucose consumption by the preclinical tumour, we used data from the Apolipoprotein MOrtality RISk (AMORIS) (n = 528,580) and the Metabolic syndrome and Cancer project (Me-Can) cohorts (n = 269,365). We identified individuals who were followed for a maximum of 15 years after their first blood glucose test until glioma diagnosis, death, emigration or the end of follow-up. Hazard ratios (HRs), 95% confidence intervals (CIs) and their interactions with time were estimated using Cox time-dependent regression. As expected, pre-diagnostic blood glucose levels were inversely related to glioma risk (AMORIS, P trend = 0.002; Me-Can, P trend = 0.04) and pre-diagnostic diabetes (AMORIS, HR = 0.30, 95% CI 0.17 to 0.53). During the year before diagnosis, blood glucose was inversely associated with glioma in the AMORIS (HR = 0.78, 95% CI 0.66 to 0.93) but not the Me-Can cohort (HR = 0.99, 95% CI 0.63 to 1.56). This AMORIS result is consistent with our hypothesis that excess glucose consumption by the preclinical tumour accounts for the inverse association between blood glucose and glioma. We discuss additional hypothetical mechanisms that may explain our paradoxical findings.
Keywords: *Blood Glucose/me [Metabolism]; *Brain Neoplasms/di [Diagnosis]; *Diabetes Mellitus, Type 2/di [Diagnosis]; *Glioma/di [Diagnosis]; *Prediabetic State/di [Diagnosis]; Adult; Aged; Biomarkers; Biomarkers/bl [Blood]; Blood Glucose; Brain Neoplasms; Brain Neoplasms/bl [Blood]; Brain Neoplasms/mo [Mortality]; Brain Neoplasms/pa [Pathology]; Diabetes Mellitus, Type 2; Diabetes Mellitus, Type 2/bl [Blood]; Diabetes Mellitus, Type 2/mo [Mortality]; Diabetes Mellitus, Type 2/pa [Pathology]; Female; Glioma; Glioma/bl [Blood]; Glioma/mo [Mortality]; Glioma/pa [Pathology]; Humans; Longitudinal Studies; Male; Middle Aged; Prediabetic State; Prediabetic State/bl [Blood]; Prediabetic State/mo [Mortality]; Prediabetic State/pa [Pathology]; Prognosis; Proportional Hazards Models; Risk Factors; Time Factors; adult; aged; biological marker; blood; brain tumor; dept.pch; female; glioma; glucose blood level; human; impaired glucose tolerance; longitudinal study; male; metabolism; middle aged; mortality; non insulin dependent diabetes mellitus; pathology; peer-reviewed; prognosis; proportional hazards model; risk factor; time factor